Epidemiology and trends in non-fatal self-harm in three centres in England, 2000–2012: findings from the Multicentre Study of Self-Harm in England - Geulayov, Galit; Kapur, Navneet; Turnbull, Pauline; Clements, Caroline; Waters, Keith; Ness, Jennifer; Townsend, Ellen; Hawton, Keith (BMJ Publishing Group Ltd, 2016)
Objectives: Self-harm is a major health problem in many countries, with potential adverse outcomes including suicide and other causes of premature death. It is important to monitor national trends in this behaviour. We examined trends in non-fatal self-harm and its management in England during the 13-year period, 2000–2012.